Modeling the precise interaction of glioblastoma with human brain region-specific organoids - Qi Fan; Hanze Wang; Tianyi Gu; Huihui Liu; Peng Deng; Bo Li; Hui Yang; Ying Mao; Zhicheng Shao (iScience, 2024)
Summary: Glioblastoma is a highly aggressive malignant tumor of the central nervous system, but the interaction between glioblastoma and different types of neurons remains unclear. Here, we established a co-culture model in vitro using 3D printed molds with microchannels, in which glioblastoma organoids (GB), dorsal forebrain organoids (DO, mainly composed of excitatory neurons), and ventral forebrain organoids (VO, mainly composed of inhibitory neurons) were assembled. Our results indicate that DO has a greater impact on altered gene expression profiles of GB, resulting in increased invasive potential. GB cells preferentially invaded DO along axons, whereas this phenomenon was not observed in VO. Furthermore, GB cells selectively inhibited neurite outgrowth in DOs and reduced the expression of the vesicular GABA transporter (VGAT), leading to neuronal hyperexcitability. By revealing how glioblastoma interacts with brain cells, our study provides a more comprehensive understanding of this disease.